2012
DOI: 10.3851/imp2470
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic HCV antibody assays

Abstract: Approximately 4.1 million Americans have been infected with HCV and 45-85% of chronically infected persons are unaware of their status. Rapid anti-HCV assays can assist and expedite the identification of those unaware of their infection. Performance characteristics of pre-market rapid anti-HCV assays (Chembio, MedMira and OraSure) have been evaluated. Their sensitivity (78.9-99.3%) and specificity (80-100%) varied. Future investigations could include evaluation of rapid anti-HCV tests in persons who are coinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In 17 studies, the type of specimen tested was serum alone [ 12 , 23 , 24 , 26 – 31 , 33 , 36 , 40 , 44 , 46 49 ]. Plasma alone was tested in three studies [ 34 , 50 , 51 ], whole blood alone was tested in 5 studies [ 25 , 32 , 35 , 37 , 45 ], oral fluid alone was tested in one study [ 42 ], oral fluid plus serum was tested in one study [ 43 ], and oral fluid plus whole blood was tested in one study [ 41 ]. The remaining two studies tested other combinations of those specimens [ 38 , 39 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 17 studies, the type of specimen tested was serum alone [ 12 , 23 , 24 , 26 – 31 , 33 , 36 , 40 , 44 , 46 49 ]. Plasma alone was tested in three studies [ 34 , 50 , 51 ], whole blood alone was tested in 5 studies [ 25 , 32 , 35 , 37 , 45 ], oral fluid alone was tested in one study [ 42 ], oral fluid plus serum was tested in one study [ 43 ], and oral fluid plus whole blood was tested in one study [ 41 ]. The remaining two studies tested other combinations of those specimens [ 38 , 39 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study tested all samples twice [ 28 ]. The results of the index tests were independently read by more than one technician in five studies [ 12 , 29 , 30 , 40 , 41 ]. Eight studies received funding from, or reported another financial relationship with the pharmaceutical industry [ 25 , 28 , 34 , 38 , 42 , 46 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for enhancing HCV diagnosis has acutely become more pertinent as a result of the availability of highly effective Direct Acting Antiviral (DAA) treatment [4]. On a worldwide basis, an estimated 80–85% of individuals with chronic infection are unaware of their infection [5, 6], although this figure may be somewhat lower in the UK, and among those with a diagnosis a minority currently receive treatment.…”
Section: Introductionmentioning
confidence: 99%